Specific Air Pollution in Road Tunnels - Licbinsky, R.; Huzlik, J.; Frybort, A.; Jedlicka, J.; Kreislova, K. (Transactions on Transport Sciences, 2013)
Negative effects of air pollution are, apart from the adverse effects on human health, also associated with damaging material goods which is manifested in e.g. the shorter service life of construction materials and faster material corrosion. Road tunnel environment is very specific since the emissions of passing vehicles are not dispersed into the surroundings and materials in the tunnel are thus immediately exposed to the pollutants produced by traffic. This paper presents the first results of measurements of specific air pollution in road tunnels of the project No TA01031043 "Quantification of specific pollution effect on materials and corrosion protection in tunnels". The total concentration of nitrogen oxides was higher in the first sampling campaign. Nitrogen dioxide concentration was higher in the second sampling campaign that corresponds to a higher traffic intensity. H2S and SO2 concentrations were almost similar in both campaigns. Higher PM2.5 concentrations were measured in the second sampling campaign that corresponds to higher traffic intensity associated with higher fine particle emissions from combustion processes. Lower PM10 concentrations in the second sampling campaign were measured probably due to the conversion of some particles to a gaseous phase due to a higher temperature and humidity. The concentrations of all measured pollutants were typically changed in between local minimal values and local maximum values in relation to daytime, or traffic volume, respectively. The particle size distribution showed in both campaigns a dominant share of coarse PM fraction PM2.5-10 but also its very high fluctuation in time. The highest share of coarse fraction was determined in the time of rush hours in the morning, as opposed to the lowest share during the night time.
Keywords: Road tunnel; emission; nitrogen oxides; particulate matter.